More research ideas for young scientists - Barr, George, 1907-; Waltrip, Mildred (New York : McGraw-Hill, 1961)
Experiments to do at home using simple materials and accurate scient ific methodology. Covers such topics as astronomy, weather, your body, and measurement.
Keywords: Science -- Experiments -- Juvenile literature. -- Juvenile literature. -- Juvenile literature. -- Juvenile literature. -- Juvenile literature; Science -- Juvenile literature. -- Juvenile literature. -- Juvenile literature. -- Juvenile literature. -- Juvenile literature